"Chance Takers Are Accident Makers": Are Patients With Epilepsy Really Taking a Chance When They Drive?. Issue 4 (July 2019) - Joshi, Charuta N.; Vossler, David G.; Spanaki, Marianne; Draszowki, Joseph F.; Towne, Alan R.; ,
This review compiles scientific data about the real dangers faced by people with epilepsy (PWE) who drive. Those include risks of motor vehicle accidents (MVA) in PWE as compared with controls (individuals without epilepsy) and as compared with persons with other medical conditions that impact fitness to drive. Data regarding Accident rates as related to seizure free intervals (SFI), single vs. multiple seizure events, and/or antiseizure drug (ASD) taper and reintroduction are discussed. Variation in state, national, and international laws and guidance for non-commercial and commercial drivers is highlighted, along with some related reasons for driving restrictions. The review concludes by emphasizing the importance of physicians educating patients about local driving laws and about risks of ASD non-adherence. The need for a broader, multi-stakeholder re-examination of driving regulations for PWE is noted.